Understanding Travel Behavior and Sustainability of Current Transportation System for Older Adults in Malaysia: A Scoping Review - Mohammed Noor, Nur Farhana; Kadir Shahar, Hayati; Hamid, Tengku Aizan; Zainalaludin, Zumilah; Ahmad, Siti Anom; Rokhani, Fakhrul Zaman; Ujang, Norsidah; Md Yusoff, Irwan Syah; Nor Akahbar, Siti Aisyah (MDPI AG, 2022)
Rapid transportation development may be welcomed by many, but older adults might find it difficult to keep up with their transportation uses and remain active. This study reviewed published articles on the travel behavior of older adults in Malaysia and associated transportation determinants to explore how sustainable the transportation system is for this vulnerable cohort. The authors searched four databases: PubMed, Scopus, ProQuest, and EBSCOhost. Inclusion criteria were older respondents, living in a community in Malaysia, addressing any travel behavior characteristics, and being written in English. Review papers, letters, book citations, comments, editorials, and experimental and animal studies are excluded from this study. A total of seven studies were included in this review extending from 2007 to 2020. The result showed that the transportation use of older adults has shifted from relying on public transport to driving their own vehicles to move around. According to the findings of this study, besides personal and health factors, the transport use of older adults is affected mainly by cost, public transport availability, road traffic and safety, the complexity of the transportation system, distance to public transit, availability of parking space, as well as road conditions and signage. It is concluded that an effective strategy to improve the transportation system is needed to prevent the unmet travel needs of older adults in Malaysia.